"Out" in the field. Reflecting on the dilemmas of insider status on data collection and conducting interviews with gay men. Issue 5 (10th June 2014) - Roberts, Simon
Abstract : Purpose: – The purpose of this paper is to explore using a reflexive approach the impact of author's personal positioning on issues of power balance between the interviewer and the interviewee, dealing with sensitive stories and concerns of difference and sameness between participants and the researcher in both the data collection process and also during the interviews. Design/methodology/approach: – Initial data were gathered from 45 semi-structured interviews with self-identified gay men in a wide range of occupations and ages working in the seaside resort of Bournemouth on the south coast of England. Findings: – The paper highlights some of the dilemmas of insider status and doing research on gay men. These include: ethical issues of closeness and involvement with participants, dealing with author's own personal frustrations, tackling the power imbalance between the interviewer and the interviewee and the impact of author's personal positioning on the data collection. Originality/value: – Little research has been done on the impact of men doing research on issues of diversity. In particular, this paper re-examines the power balance between the interviewer and interviewee as being one sided as previous studies have suggested in the researcher's favour. It also uncovers ethical dilemmas such as sexual attraction and involvement that has had scant coverage in the literature.